Esthetic anterior prosthetic rehabilitation in primary dentition. Case report - Loo-Valle, Jennifer (2024)
Objective: To describe a prosthetic rehabilitation with a telescopic prosthesis to improve child’s self -steem. Case report: A female 4-year-5-month-old patient attended the Dental Clinic of the Universidad Científica del Sur, Lima-Peru along with her parents. They requested treatment due to dental caries lesions that affected their daughter’s self-esteem. Oral clinical examination and radiographs revealed early childhood caries. After assessing the diagnosis, the former dental treatment was planned for the child. The treatment included dental prophylaxis, hygiene guidelines, restorations and pulp therapy. Also, it was planned to place a telescopic prosthesis replacing 51. Conclusion: Anterior aesthetic prosthetic rehabilitation is a good alternative to the premature loss of deciduous upper anterior teeth since it restore aesthetics, improve phonation. GMoreover, it has a good acceptance and a positive impact on child's self-steem.